Hubungan Kewarganegaraan dan Negara Dalam Prespektif Urgensi Kewargangeraan - Wahyuningrum, Kartika (JURNAL YURIDIS UNAJA, 2024)
Citizenship is every person who according to citizenship law is a citizen. To understand the issue of citizenship, both apatride and bipatride, it is also necessary to study the two principles of citizenship, namely the principles of jus soli and jus sangui-nus. The problem of this research is. What is the relationship between citizenship and the state? This is because with a good understanding of citizenship, the life of the nation and state will become peaceful and clear. And we as citizens who are responsible for society, nation and state, we should try to improve its practice. the noble principles and values of the nation, especially understanding that humans basically have the same dignity and worth as creatures created by God, in order to create justice in the life of the nation.